Fab Lab Toys From a Second-Grade Industrial Design Studio: Expanding the Boundaries of Toy Design - Talu, Nilüfer; Talu,N.; Yurt,C.; Çolak,C. (Common Ground Research Networks, 2024)
This study delves into the seven-week toy design process within a second-grade industrial design undergraduate studio. The foundation of this studio lies in a creative design brief that centers on a closely interconnected triad of concepts: opportunity, challenge, and expectation. The Fab Lab environment serves as an ideal platform and opportunity for generating toy designs within the realm of design education. The intention is to challenge the conventional landscape of mass-produced toys and prevalent toy categories in consumer culture through Fab Lab–produced toys. The expectation is to design toys that transcend these established categories, catering more effectively to the unstructured playtime of children aged 3 to 6. This process aspires to harness contemporary technologies like 3D printing in design education to equip students with skills not only for tackling novel and present challenges but also for addressing critical contexts. The symbiotic relationship between the design education process and experiential prototyping elevates students’ understanding of real-world implications and nurtures their creativity within the design journey. The culmination of this process yields multi-category toy designs poised to enrich the free play experiences of children aged 3 to 6. © 2024 Common Ground Research Networks. All rights reserved.
Keywords: 3D Printing; Creative Design Brief; Design Education; Fab Lab; Prototyping; Toy Design